Characterisation of a novel chicken-derived H3N3 avian influenza virus detected in China in 2023: Pathogenicity and immunogenicity - Yan Wang; Ya-dong Gao; Cheng-hui Jiang; Yao Xi; Ming-xuan Yang; Wei Zhang; Yang-yang Pan; Qiao-ying Zeng (PLoS ONE, 2025)
The poultry industry faces a constant threat from the mutation and transmission of avian influenza viruses (AIVs). While waterfowl and wild birds are natural hosts of H3N3 AIV, reports of H3N3 infections in chickens are limited. However, in 2023, a decline in egg production among laying hens in the Yancheng Region of Jiangsu Province prompted a study. This research aimed to diagnose the aetiology in laying hens through molecular virological methods and characterise the biological properties of the causative pathogens. An H3N3 AIV subtype strain, A/chicken/China/YC01/2023(H3N3), was isolated from chickens exhibiting lesions. Genome sequencing and analysis revealed a novel genetic makeup: the HA gene originated from an H3N8 AIV, the NA gene from an H10N3 AIV, and the internal genes from an H9N2 AIV, all circulating in China. Chickens experimentally infected with the isolate showed signs of Harderian gland haemorrhage, nasal mucus, tracheal circumferential bleeding, and lung bleeding and localised necrosis. Histopathological examination confirmed nasal mucosal and tracheal inflammation, lung capillary congestion, liver cell damage, and sparse splenic lymphocytes. Viral shedding was significantly higher in the oropharyngeal cavity, peaking 2–6 days post-infection, compared to the cloaca. For the first time, the immunogenicity of a novel chicken-derived H3N3 subtype AIV was assessed in specific pathogen-free chickens. An inactivated vaccine, prepared from the isolated strain, resulted in antibody titres peaking at 9.6 log2 four weeks after immunization. Furthermore, challenges with either the isolated strain or a duck-origin BZ01/2023(H3N3) strain after immunisation did not cause clinical signs or viral shedding on day 4. In conclusion, the isolate H3N3 AIV can replicate in chickens, leading to organ damage and pathogenicity. Crucially, the inactivated vaccine derived from this isolate is highly immunogenic and provides cross-protection against the duck-derived strain.